Rancang Bangun Sistem Informasi Stock Barang Berbasis Website Pada PT. XYZ - Sitepu, Firmansyah; Ramadhan, Mulia; Bahari, Syahrial (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
The development of information technology has facilitated the creation of applications to enhance productivity across various sectors. However, the utilization of this technology has not been fully optimized, including in the TEKPOL Division of PT. Perkebunan Nusantara III. Data management in the TEKPOL Division is still performed manually using Microsoft Excel, which makes it difficult for administrators to manage data in a structured and efficient manner. This study aims to design and develop an information system for managing goods data to assist administrators in the TEKPOL Division in organizing, storing, and accessing data more easily and systematically. The system was developed using PHP as the programming language, Bootstrap 5 as the framework for the interface, and MySQL as the database for data processing. The result of this development is an information system with a user-friendly interface that enhances efficiency and accuracy in managing goods data in the TEKPOL Division. Therefore, this system is expected to provide an effective solution in supporting administrative activities at PT. Perkebunan Nusantara III.